Utopian Dreams : Postmodernism, Imperialism, and the Search for Meaning in Iain M. Banks’ Culture series - Uusilehto, Eino (My University, 2025)
In this thesis, I discuss postmodernism and imperialism in Iain M. Banks’ Culture series. My aim is to analyse the postmodern nature and imperialist practices of the Culture, the central utopian society of the series. I base my analysis primarily on the first four novels of the series. The purpose of this thesis is to showcase a link between the postmodern aspects of the Culture and its imperialism. I analyse the Culture’s postmodernism in terms of posthumanism, hyperreality, and fragmentation based on a wide array of previous writing on postmodernism. My analysis of imperialism in the series is based on the framework of modernisation theory as well as Antonio Gramsci’s work on hegemony. Over the course of my thesis, I explain how the postmodern aspects of the Culture form a system of values that both justifies and enables the Culture’s imperialist conduct in relation to other societies. I also show that the Culture’s imperialism is fundamentally driven by a search for purpose. The Culture’s posthumanism is most visible in the technological augmentation of its people as well as in the symbiotic relationships of its biological and mechanical citizens. The Culture’s hyperreality is evident both from its tendency to gamify reality and from its general veneration of simulacra and simulations over reality. This is exemplified by the significance of games as a recurring motif in the series. The third postmodern aspect, fragmentation, is relevant in regard to the peripheral sub-cultures of the Culture Ulterior. These aspects together show the Culture as fundamentally postmodern. Furthermore, they show how Culture identity is irremovable from Culture products, and that these products embody and spread the Culture everywhere they are. The Culture spreads through the galaxy via its products, but it also practices active imperialism via the departments of Contact and Special Circumstances. These departments work together to incorporate other societies into the Culture on the pretence that the spread of the Culture is the common good for all. Although its imperialism has a seemingly benevolent aim in the enforcement of prosperity, the Culture is willing to use any means necessary to achieve its goals. As such, the Culture’s morally dubious actions are justified by its self-defined correct worldview and the moral imperative to expand and spread its utopian values.
Keywords: Iain M. Banks, Culture series, Postmodernism, Posthumanism, hyperreality, imperialism, hegemony